Himala - Lee, Ricardo; Bernal, Ishmael; Jarlego, Ike; Carballo, Bibsy M.; Concio, Charo Santos-; Aunor, Nora (Experimental Cinema of the Philippines, 1982)
Story of a young woman believed to have miraculous powers who transforms a sleepy barrio into a commercial center.